2013
DOI: 10.1089/ars.2012.5089
|View full text |Cite
|
Sign up to set email alerts
|

Human Hp1-1 and Hp2-2 Phenotype-Specific Haptoglobin Therapeutics Are Both Effective In Vitro and in Guinea Pigs to Attenuate Hemoglobin Toxicity

Abstract: The present data do not provide support for the concept that phenotype-specific Hp therapeutics offer differential efficacy in mitigating acute Hb toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 42 publications
3
82
0
3
Order By: Relevance
“…Hb a and b subunits, however, were detected in the cell lysates (41,42). Although it is possible that some Hb is bound to cell membrane, up-regulation of HO-1 is a strong indication of the internalization of the protein in our experiment.…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 61%
“…Hb a and b subunits, however, were detected in the cell lysates (41,42). Although it is possible that some Hb is bound to cell membrane, up-regulation of HO-1 is a strong indication of the internalization of the protein in our experiment.…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 61%
“…Studies presented here are restricted to the multimeric Hp phenotype. However, based on earlier studies, in which we confirmed that monomeric and multimeric have identical activity against Hb-triggered hypertension, we do not assume that this polymorphism would significantly affect the compartmentalization function of Hp (24).…”
Section: Discussionmentioning
confidence: 74%
“…The identity, purity, and function of the protein were confirmed by liquid chromatography-tandem mass spectrometry (LC-MS/MS), polyacrylamide gel electrophoresis, and surface plasmon resonance as described (24). Hemoglobin was purified from outdated blood, as previously described (24). Hb concentrations were determined by spectrophotometry and are given as molar concentration of total heme (1 M Hb tetramer is therefore equivalent to 4 M heme).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once bound to Hb, several functions of Hp are responsible for its tissue protective effects [5,6]. One of the essential functions of Hp is to attenuate Hb-induced oxidative damage.…”
Section: Introductionmentioning
confidence: 99%